Mechanical properties of polymethyl methacrylate as a denture base: Conventional versus CAD-CAM resin – A systematic review and meta-analysis of in vitro studies - de Oliveira Limírio, João Pedro Justino [UNESP]; Gomes, Jéssica Marcela de Luna [UNESP]; Alves Rezende, Maria Cristina Rosifini [UNESP]; Lemos, Cleidiel Aparecido Araújo; Rosa, Cleber Davi Del Rei Daltro [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2021)
Statement of problem: The development of polymethyl methacrylate (PMMA) computer-aided design and computer-aided manufacturing (CAD-CAM) resin blocks with reported improved mechanical properties has simplified complete denture production. However, whether the objective of improved mechanical properties has been achieved compared with conventional heat-polymerized PMMA is not yet clear. Purpose: The purpose of this systematic review and meta-analysis was to evaluate the mechanical properties of denture base resins manufactured by conventional heat-polymerization and by CAD-CAM in terms of flexural strength, flexural modulus, and surface roughness. Material and methods: Electronic databases (PubMed/MEDLINE, Scopus, Web of Science) were independently searched by 2 researchers for relevant studies published up to November 2020. The population, intervention, comparison, and outcome (PICO) question was, “Does the conventionally manufactured, heat-polymerized PMMA resin, as a denture base, demonstrate the same mechanical properties as the CAD-CAM resin block?” In addition, a meta-analysis was based on the inverse variance method. Flexural strength, flexural modulus, and surface roughness were analyzed through the continuous outcome evaluated by mean difference and standard deviation, with 95% confidence intervals. To evaluated heterogeneity, the I2 value (≤25%=low, ≥50%=moderate and ≥75%=high) and the P value were considered. P<.10 indicated statistical difference for heterogeneity. The effects of meta-analysis were based on the results of heterogeneity as per the studies. Results: Thirteen in vitro studies were included in the analysis. A total of 507 specimens were evaluated, 222 conventional and 285 CAD-CAM. In terms of flexural strength, the data showed no significant difference when conventional heat-polymerized PMMA was compared with CAD-CAM PMMA resins (P=.06; mean difference=18.28; 95% confidence interval:-0.42 to 36.97). In terms of flexural modulus, there was a significant difference for the CAD-CAM PMMA group (P=.01; mean difference=589.22; 95% confidence interval: 117.95 to 1060.48). In terms of surface roughness, a significant difference was observed between the groups (P=.02; mean difference=-0.53; 95% confidence interval: -0.97 to -0.09) with the conventional heat-polymerized PMMA resin having higher surface roughness values. Conclusions: The mechanical properties of CAD-CAM PMMA resins were generally improved when compared with heat-polymerized polymethyl methacrylate resin.